Health and mental health needs and experiences of minority clients in Portugal - Moleiro, C.; Junça Silva, A.; Borges, V.; Ferreira, R. (International Journal of Migration, Health and Social Care, 2009)
The paper addresses diversity, multi?culturalism and mental health. It reports qualitative data from a larger project on multi?cultural counselling competencies in Portugal which sought to meet the needs identified by specific minority groups by developing integrative, responsive and culturally sensitive treatments. A qualitative study is presented, with the aim of exploring the representations of mental health and illness held by ethnic minority groups in Portugal, as well as their specific needs and obstacles encountered in their interactions with health professionals. Semi?structured interviews were conducted, and the results indicate that the meanings of health and mental health varied. Meanings of psychological health were related to general well?being. Help?seeking behaviours were associated with providing and receiving family and social support, mainly among participants of African descent. Although the great majority of participants had had no experience of counselling or psychotherapy, they expected psychologists to be multiculturally sensitive, as well as knowledgeable about diversity and multi?culturalism. Implications for development of mental health services for minority clients are discussed.